Meta analysis of ovulation induction effect and pregnancy outcome of acupuncture & moxibustion combined with clomiphene in patients with polycystic ovary syndrome - Yang, Lijie; Yang, Wanqiu; Sun, Minghan; Luo, Linjie; Li, Hong Ru; Miao, Runqing; Pang, Li; Chen, Yajie; Zou, Kun (Frontiers in Endocrinology, 2023)
Objective Using Mesh Meta Analysis to evaluate the efficacy of Acupuncture & Moxibustion, Clomiphene, Acupuncture & Moxibustion combined with Clomiphene for treating Polycystic Ovary Syndrome (PCOS), in order to provide evidence-based medical evidence for whether to recommend Acupuncture & Moxibustion or Combine western medicine to treat PCOS. Methods Eight databases including The Cochrane Library, Pubmed, Embase, Web of Science, CNKI, Wanfang Date, VIP and CBM were searched by computer. The included research period is from the establishment of the database to May 2023, which concerned with randomized controlled trials involving Acupuncture & Moxibustion, Clomiphene, Acupuncture & Moxibustion combined with Clomiphene on ovulation induction and pregnancy outcome in patients with PCOS. The duration of the research paper is from 2016 to 2023.The inclusion criteria refer to the Rotterdam standards issued by the European Center for Human Reproduction and Embryology and the American Society of Reproductive Medicine in January 2003, or the Expert Consensus on the Diagnosis and Treatment of Polycystic Ovarian Syndrome by the Endocrinology Group of the Obstetrics and Gynecology Branch of the Chinese Medical Association. Simultaneously exclude related diseases, repetitive literature, as well as literature with incomplete abstract information and no original data provided. Two researchers independently screened the literature, extracted data, and evaluated the risk of bias included in the study, using Stata17.0 software for a mesh meta-analysis. Results Six randomized controlled trials were included, covering 1410 PCOS patients. Three interventions included Acupuncture & Moxibustion, Clomiphene, Acupuncture & Moxibustion combined with Clomiphene. Mesh Meta Analysis showed that in terms of improving ovulation rate, there was no statistical difference between Acupuncture & Moxibustion (A), Clomiphene (B), Clomiphene combined with Acupuncture & Moxibustion (C) (P>0.05).Acupuncture & Moxibustion (A) versus Clomiphene (B) [MD=0.15,95% CI (-0.51,0.80)], Acupuncture & Moxibustion (A) versus Clomiphene combined with Acupuncture & Moxibustion (C) [MD=1.60,95% CI (0.97,2.23)], Clomiphene (B) versus Clomiphene combined with Acupuncture & Moxibustion (C) [MD=1.45,95% CI (0.91,1.99)]. In terms of pregnancy outcome, the difference between the three intervention methods was statistically significant (P<0.05). Acupuncture & Moxibustion (A) versus Clomiphene (B) [MD=-0.80,95% CI (-1.84,0.23)], Acupuncture & Moxibustion (A) versus Clomiphene combined with Acupuncture & Moxibustion (C) [MD=0.29,95% CI (-0.73,1.30)], and Clomiphene (B) versus Clomiphene combined with Acupuncture & Moxibustion (C) [MD=1.09,95% CI (0.39,1.79)], The order of pregnancy rate from high to low is Acupuncture & Moxibustion combined with Clomiphene (C), Acupuncture & Moxibustion (A), Clomiphene (C).In terms of influencing endometrial thickness, the difference between the three intervention methods was statistically significant (P<0.05). Acupuncture & Moxibustion (A) versus Clomiphene (B) [MD=-0.84,95% CI (-1.87,0.19)], Acupuncture & Moxibustion (A) versus Acupuncture & Moxibustion combined with Clomiphene (C) [MD=0.26,95% CI (-1.01,1.53)], Clomiphene (B) versus Acupuncture & Moxibustion combined with Clomiphene (C) [MD=1.10,95% CI (0.36,1.84)], Acupuncture & Moxibustion combined with Clomiphene (C) has the best effect on improving endometrial thickness. In subgroup analysis, the effect of Acupuncture & Moxibustion treatment frequency on ovulation rate and pregnancy rate was not statistically significant. The combination of Acupuncture & Moxibustion, Electroacupuncture and warm Acupuncture & Moxibustion has no effect on the pregnancy rate, but the combination of Electroacupuncture and Clomiphene has the best effect on improving the ovulation rate. In the observation of adverse reactions, compared with clomiphene alone, Acupuncture & Moxibustion combined with Clomiphene can reduce the occurrence of Luteinized Unruptured Follicle Syndrome (LUFS) and Ovarian Hyperstimulation Syndrome (OHSS), and reduce the occurrence of physical adverse reactions such as nausea, vomiting, headache and dermatitis. Conclusion Acupuncture & Moxibustion is effective in improving the ovulation promoting effect and pregnancy outcome of PCOS patients. The ovulation promoting effect of Acupuncture & Moxibustion or combined with Clomiphene is similar to that of Clomiphene alone, but Acupuncture & Moxibustion combined with Clomiphene has more advantages in improving the pregnancy rate of PCOS, and it also can reduce the adverse reactions of Clomiphene alone. Acupuncture & Moxibustion can be used as a recommended treatment for PCOS. More cases should also be included in the subgroup analysis to study the impact of Acupuncture & Moxibustion programs on clinical efficacy and further optimize the Acupuncture & Moxibustion treatment program. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier (CRD42023433057).